2021
DOI: 10.30573/ks--2021-dp09
|View full text |Cite
|
Sign up to set email alerts
|

Saudi Non-oil Exports Before and After COVID-19: Historical Impacts of Determinants and Scenario Analysis.

Abstract: The diversification of the non-oil sector, including its exports, is at the core of Saudi Vision 2030. This study investigates Saudi non-oil exports in a novel way. Specifically, it differs from previous studies on this topic owing to its modeling framework. This study’s modeling framework first estimates the non-oil export equation, which allows us to examine the historical impacts of theoretically articulated demand- and supply-side determinants on non-oil exports. This is done using Autometrics, a state-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The Saudi economy can also be improved through technology transfers to key research centers. A study by Hasanov et al (2021) explored the critical components of the KSA's long-and short-term non-oil exports. The study informed the policy-making process and provided insights into Vision 2030 by developing a state-of-the-art model framework for non-oil exports (Hasanov et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Saudi economy can also be improved through technology transfers to key research centers. A study by Hasanov et al (2021) explored the critical components of the KSA's long-and short-term non-oil exports. The study informed the policy-making process and provided insights into Vision 2030 by developing a state-of-the-art model framework for non-oil exports (Hasanov et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Hasanov et al (2021) explored the critical components of the KSA's long-and short-term non-oil exports. The study informed the policy-making process and provided insights into Vision 2030 by developing a state-of-the-art model framework for non-oil exports (Hasanov et al, 2021). McKinsey Global Institute (2015 revealed that the KSA's economy, which has substantially grown over the last several years as a result of increasing oil prices, is now in a transition phase.…”
Section: Literature Reviewmentioning
confidence: 99%